THE INFLUENCE OF LOCUS OF CONTROL, TURNOVER INTENTION AND AUDITOR PERFORMANCE ON DYSFUNCTIONAL AUDIT BEHAVIOR WITH ORGANIZATIONAL COMMITMENT AS A MODERATING VARIABLE ON AUDITORS IN PUBLIC ACCOUNTING FIRMS IN MEDAN AND PEKANBARU - Panjaitan, Edwin Jonathan (Asosiasi Dosen Akuntansi Indonesia, 2019)
This study aims to examine the influence of Locus of Control, Turnover Intention, Auditor Performance on Dysfunctional Audit Behavior. The indicators used to measure the Dysfunctional Audit Behavior are premature sign off, underreporting of time audits, replacement of audit procedures.This study took a sample at the Public Accountant Firmsrepresenting Medan and Pekanbaru which was registered with the Indonesian Institute of Certified Public Accountants in 2019. The method used was the Purposive Sampling method. Data analysis was carried out by data quality test and hypothesis testing used by multiple linear regression methods.The results of this study indicate that the three independent variables, namely Locus of Control, Turnover Intention and Auditor Performance simultaneously influence the Dysfunctional Audit Behavior, at P <0.05 (P = 0,000). The results of the study partially indicate that Locus of Control has a positive and significant effect on the Dysfunctional Audit Behavior, at P <0.05 (P = .015) with an effect of (ß = 0.280). Turnover Intention has a positive and significant effect on the Dysfunctional Audit Behavior, at P <0.05 (P = .011) with an effect of (ß = 0.726). Auditor performance has a positive and significant effect on the Dysfunctional Audit Behavior, at P <0.05 (P = .003) with an effect of (ß = 0.328). Moderating variables in this study are Organizational Commitment capable of moderating partially Locus of Control with a significance of 0.010, Turnover Intention with a significance of 0.026 and Auditor Performance with a significance of 0.033 to Dysfunctional Audit Behavior.